Detection and Identification of Fungal Diversity Associated with Soybean (Glycine max (L.) Merrill) Seeds from the United States with Blotter Testing Method - Haffi, Nur Muhammad; Isminingsih, Sulastri; Susiyanti; Saylendra, Andree (Jurnal Agroekoteknologi Terapan, 2025)
Soybeans are one of the favorite commodities of the Indonesian people. Soybeans, as a potential agricultural product, need to be increased in production because they are the main source of protein for most families in Indonesia. This study aims to detect and identify the diversity of fungi carried by soybean seeds (Glycine max (L.) Merril) from the United States using the Blotter Testing method on different substrate variations. The method used in this study is a qualitative descriptive approach, incorporating observational methods. This study employed a non-factorial Randomized Block Design (RBD) with three substrates: Filter Paper (S1), Opaque Paper (S2), and Kitchen Tissue (S3). The study's results identified two types of fungi in soybean seeds from the United States through blotter testing, based on morphological characteristics: Rhizopus sp. and Aspergillus sp. Notably, Aspergillus sp. was found with the highest frequency. The application of the blotter method using filter paper gave the best results in identifying fungi based on the high frequency of fungal findings. The presence of both types of fungi indicates that soybeans are dangerous for consumption because they contain Aflatoxin compounds. Keywords: Fungi, blotter method, soybeans